The Social Media Overture of the Pan-European Anti-ACTA Protest: An Empirical Examination of Coordination in Connective Action - Mercea, Dan; Funk, Andreas; Nixon, Paul (AoIR Selected Papers of Internet Research, 2013)
This paper proposes an empirical model designed to operationalize the notion of digitally and loosely coordinated collective action as proposed by the recent theory of connective action. To show how the capacity for coordination of the expressive participation that is characteristic of connective action may be divided into a capacity for motivational coordination and a capacity for resource coordination, respectively. These two dimensions of coordination may enable us to discern how individual motives and collective goals can become aligned through expressive participation in connective action. The paper provides preliminary findings that support the two dimensionality of coordination.